Impacto ambiental do fósforo em rações para tilápia do Nilo (Oreochromis niloticus) - Bueno, Guilherme Wolff (2011)
The relationship between men and environment has always been marked by anthropocentric logic, in which distinguishes man from nature and is elevated to the title and source of all other values. Under this logic, man has caused many environmental impacts, bringing to society some irreversible damages. However, this view is being increasingly criticized and revised. The global tension facing the responsibility in producing in a sustainable way, given that water resources are limited, drives a new global context, which requires a different way of thinking and acting. Therefore, the activity represented by aquaculture producers and entrepreneurs, feed mills, regulatory agencies, educational and research institutions may establish codes of conduct and environmentally responsible management practices in order to minimize the environmental impacts of animal production. Therefore, the objective of this study consisted of two experiments to determine the environmental impact in the aquatic environment of phosphorus in diets for juvenile Nile tilapia (Oreochromis niloticus). In this context, the first experiment discusses the influence of different levels of phosphorus in the diet and the emission of effluents from the fish culture. We used 120 juvenile O. niloticus with mean weight of 85.11 ± 0.34 g to evaluate two levels (0.8 and 1.2%) of total phosphorus in the diet, to determine the apparent digestibility of phosphorus in the diets using chromic oxide (Cr2O3) incorporated in the rate of 0.1% in the diets. And to verify how the use of different ingredients in the diet will meet the requirements for tilapia and the total phosphorus in wastewater generation, total phosphorus digestibility, pellets stability in water, and minerals leaching in water from the diet were evaluated and quantified the waste generated to produce a ton of tilapia. Six isonitrogenous and isocaloric diets were formulated containing 28% crude protein and 3000 kcal DE / kg with levels of 0.8% of total phosphorus, using dicalcium phosphate, meat and bone meal, poultry offal meal, anchovy meal, tilapia waste and bone meal as ingredients. We conclude that the use of 0.8% of total phosphorus promotes a better control of water quality and can be used as a nutritional strategy for reducing effluent from aquaculture. As for the ingredients, the best efficiency for total phosphorus was 83.74% for dicalcium phosphate, 77.73% for anchovy meal, 75.27% for tilapia meal and 73.42% for poultry meal in diets for juvenile Nile tilapia. Therefore through a balanced animal nutrition is possible to reduce the metabolites excretion in the water, reaching an adequate fish production with less environmental impact.